A study of the influence of environment on health of the child population in Chernihiv region (Environment & Health, 2015)
Objective: assessment of the influence of environmental factors on the health indices of child population in rural areas of Chernihiv region.Materials and methods. The relationship between the level of primary and general morbidity in children of 0-14 years, stillbirth, perinatal, neonatal, postneonatal, infant mortality rates and the condition of contamination of drinking water, food, air and soil in the period of 2001-2012 was studied. Sources of information were the data of the Regional Centre for Information and Analytical Technologies, and Promoting a Healthy Lifestyle of Chernihiv Regional Council as well as the statistical form № 18 "Report on the environmental factors that affect the health of the popula? tion". A correlation analysis with the calculation of the Pearson correlation coefficient was used.Results. It was found that the leading factors that affect the health of the rural child population of Chernihiv region are the quality of drinking water by the sanitary-chemical and sanitary-bacteriological parameters, epidemiological and radiation safety of food, the quality of atmospheric air and helminthological soil pollution. Chemical pollution of food and bacteriological pollution of soil have much less influence on children's health. Between the chemical pollution of soil and the test parameters, the reliable positive connection was not revealed at all.
Keywords: environment; morbidity; prevalence of diseases; infant mortality; child population; Chernihiv region